2009
DOI: 10.4103/0973-1482.59901
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of genetic lesions in apoptosis-regulating and proliferation control genes in diffuse large B-cell non-Hodgkin′s lymphoma

Abstract: Our data suggest that simple p53 protein expression by IHC at the time of diagnosis may help to identify high-risk patients, who may benefit with more aggressive and newer treatments in addition to standard CHOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Pervez et al reported positive Bcl-2 protein expression in 75 of 117 (64.1%) patients in their study on 117 patients with DLBCL. However, there was no significant difference in OS between patients with negative or weakly positive Bcl-2 and high Bcl-2 expressions [22]. Similarly, in the present study, we did not show any difference in the outcome of patients with Bcl-2-positive or Bcl-2-negative DLBCL.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Pervez et al reported positive Bcl-2 protein expression in 75 of 117 (64.1%) patients in their study on 117 patients with DLBCL. However, there was no significant difference in OS between patients with negative or weakly positive Bcl-2 and high Bcl-2 expressions [22]. Similarly, in the present study, we did not show any difference in the outcome of patients with Bcl-2-positive or Bcl-2-negative DLBCL.…”
Section: Discussionsupporting
confidence: 55%
“…It is involved in the regulation of cell survival by interaction with G-S phase transition within the cell cycle and by induction of apoptotic cell death [17,18]. The incidence of p53 expression in DLBCL varies between 5.0% and 71.0% [5,6,7,10,14,19,20,21,22]. In the present study, p53 expression was identified in 62.9% of all cases and high p53 expression was identified in 10 patients (28.6%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of and mortality from lymphoma are higher in the Uighur ethnic group of Xinjiang than in people from eastern coastal regions. With a male to female ratio of 2.3:1, lymphoma has two peaks of incidence at younger than 10 years and 31-50 years in the population (Pervez et al, 2009). Malignant lymphoma has highly homogenous features but has various subtypes and classifications.…”
Section: Introductionmentioning
confidence: 99%